Intimate Partner Violence Against Pregnant Women: Study About The Repercussions On The Obstetric And Neonatal Results - Driéli Pacheco Rodrigues; Flávia Azevedo Gomes-Sponholz; Juliana Stefanelo; Ana Márcia Spanó Nakano; Juliana Cristina dos Santos Monteiro (SciELO, 2014)
This observational, descriptive and analytic study aimed to identify the prevalence of IPV cases among pregnant women and classify them according to the type and frequency; identify the obstetric and neonatal results and their associations with the intimate partner violence (IPV) occurrence in the current pregnancy. It was developed with 232 pregnant women who had prenatal care at a public maternity hospital. Data were collected via structured interview and in the patients' charts and analyzed through the statistic software SAS® 9.0. Among the participants, 15.5% suffered IPV during pregnancy, among that 14.7% suffered psychological violence, 5.2% physical violence and 0.4% sexual violence. Women who did not desire the pregnancy had more chances of suffering IPV (p<0.00; OR=4.32 and 95% CI [1.77 - 10.54]). With regards to the obstetric and neonatal repercussions, there was no statistical association between the variables investigated. Thus, for the study participants there were no negative obstetric and neonatal repercussions related to IPV during pregnancy.